Why Australia Prospered : The Shifting Sources of Economic Growth - McLean, Ian W. (Book collections on Project MUSE., 2012)
This book is the first comprehensive account of how Australia attained the world's highest living standards within a few decades of European settlement, and how the nation has sustained an enviable level of income to the present. Beginning with the Aboriginal economy at the end of the eighteenth century, Ian McLean argues that Australia's remarkable prosperity across nearly two centuries was reached and maintained by several shifting factors. These included imperial policies, favorable demographic characteristics, natural resource abundance, institutional adaptability and innovation, and gr.